2020
DOI: 10.1159/000505101
|View full text |Cite
|
Sign up to set email alerts
|

Colon-Targeted Therapy of Tacrolimus (FK506) in the Treatment of Experimentally Induced Colitis

Abstract: <b><i>Background/Aims:</i></b> Inflammatory bowel disease is a chronic or remitting/relapsing intestinal inflammation, which comprises Crohn’s disease and ulcerative colitis (UC). Severe UC is a life-threatening condition that requires corticosteroids (CS) as a first-line rescue therapy. Some patients are refractory to CS and may require alternative immunosuppressive therapy. Oral tacrolimus (FK506), an immunosuppressive agent, has been reported to be effective in the management of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It is often used as an excipient because it enables a pH-sensitive dissolution at about pH 7.2, allowing a specific release of the drug into the colon [ 109 ]. ES100 and ERS100 (a time-dependent polymer) were extensively used in targeted oral drug delivery systems; they were used singularly or coupled together [ 110 , 111 ] and even in the form of microspheres [ 112 ] and showed an effective response to pH changes along the gastrointestinal tract. They were exploited for IBD [ 113 ], IBS [ 114 , 115 , 116 ], and colon cancer treatments [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is often used as an excipient because it enables a pH-sensitive dissolution at about pH 7.2, allowing a specific release of the drug into the colon [ 109 ]. ES100 and ERS100 (a time-dependent polymer) were extensively used in targeted oral drug delivery systems; they were used singularly or coupled together [ 110 , 111 ] and even in the form of microspheres [ 112 ] and showed an effective response to pH changes along the gastrointestinal tract. They were exploited for IBD [ 113 ], IBS [ 114 , 115 , 116 ], and colon cancer treatments [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic activity of tacrolimus has been previously described in other animal studies, in which tacrolimus was administered orally in the form of microparticles [44] and microspheres [45] prepared with pH sensitive polymers to allow drug delivery to the colon and nanoparticles [17] with enhanced adhesion to the inflamed tissue. Thus, the present study was focused on the development of a rectal dosage form that delivers the incorporate drug content directly to the colon, avoiding the side effects derived from an undesired early drug release in upper parts of the GI tract.…”
Section: Methylprednisolonementioning
confidence: 94%
“…However, in several cases, patients with IBDs are refractory to standard drugs. A recent study showed the efficacy of the potent immunosuppressant tacrolimus (TAC; FK506 ) in the management of colitis [8]. Similarly, sirolimus (SIR), also known as rapamycin, is a macrocyclic antibiotic and potent immunosuppressant.…”
Section: Introductionmentioning
confidence: 99%